The Distributional Characteristics of M2 Macrophages in the Placental Chorionic Villi are Altered Among the Term Pregnant Women With Uncontrolled Type 2 Diabetes Mellitus - Zhang, Muqiu; Cui, Dong; Yang, Huixia (Frontiers in Immunology, 2022)
Aim：No definite conclusions have been drawn regarding how prolonged exposure to hyperglycemia affects the distribution of macrophages in the placenta, expecially in the pregnant women with uncontrolled type 2 diabetes mellitus (T2DM). Herein, we explored the distributional characteristics of placental M2 macrophages, including hofbauer cells (HBCs) in the chorionic villi and decidual macrophages, in pregnant women with uncontrolled T2DM. Methods：6 healthy singleton pregnancies and 5 uncontrolled T2DM singleton pregnancies were collected. Multicolor immunofluorescence and immunohistochemistry were performed to record M1 macrophages by CD80 and CD86, the general M2 macrophages by CD163, M2a macrophages by CD163 and DG-SIGN, M2b macrophages by CD163 and CD86, and M2c macrophages by CD163 and CD206. Meanwhile, the monocyte marker of CD14 and the general macrophage marker of CD68 were also documented on placenta. Results：In the chorionic villi and decidua, the most common infiltrated macrophages was the general M2. There were only few M1 and M2b macrophages distributing in placenta of both the healthy and uncontrolled T2DM groups. The infiltrated degree of M2c macrophages were moderate in chorionic villi and decidua. And the uncontrolled T2DM and healthy pregnant women had comparable amount of M2c macrophages infiltration in chorionic villi (p=0.158). Notely, in both of the healthy and uncontrolled T2DM pregnant women, the predominant subtype of M2 macrophages in the chorionic villi was M2a, where it mainly infiltrated around vessels and syncytiotrophoblasts. The uncontrolled T2DM pregnant women had more M2a macrophages infiltration than the healthy pregnant women (p=0.016). The M2a macrophages in the decidua of the uncontrolled T2DM group were similar to those of the normal group (p=0.800). Meanwhile, it was in the chorionic villi but not the decidua, the CD68+ macrophages and CD14+ M2a macrophages macrophages were also elevated in the uncontrolled T2DM group (p=0.035 and 0.044, respectively). Conclusion：These results confirm that the M2 macrophages exhibited increased in the chorionic villi of pregnant women with uncontrolled T2DM. The subsets of M2 macrophages in the placental decidua were similar between uncontrolled T2DM pregnant women and normal groups. It may provide a basis for exploring the functions of different subsets of macrophages in the placental chorionic villi.